Effect of brand personality on brand loyalty on Converse brand shoes with brand love as a mediation variable - Latifa Putri Anggina; Dina Patrisia (Universitas Negeri Padang, 2022)
This experiment is conducted to analyze (1) the effect of brand personality sincerity on brand loyalty on Converse brand shoes users. (2) the effect of brand personality excitement on brand loyalty on Converse brand shoes users. (3) the effect of brand personality sincerity on brand love on Converse brand shoes users. (4) the effect of brand personality excitement on brand love on Converse brand shoes users. (5) the effect of brand love on brand loyalty on Converse brand shoes users. (6) the effect of brand personality sincerity on brand loyalty mediated by brand love on Converse brand shoes users. (7) the effect of brand personality excitement on brand loyalty mediated by brand love on Converse brand shoes users. The population in this research are all generation z Converse brand shoes users and the sample in this study were all Converse brand shoes users who had use more than once. The sample size in this study was 281 respondent. The data has been collected through online questionnaire. The data has been analyzed by using partial square structural aquation modeling. The result of this study indicate that (1) Brand personality sincerity has no positive and no significant effect on brand loyalty on Converse brand shoes users. (2) Brand personality excitement has no positive and no significant effect on brand loyalty on Converse brand shoes users. (3) Brand personality sincerity has positive and significant effect on brand love on Converse brand shoes users (5) Brand love has positive and significant effect on brand loyalty on Converse brand shoes users. (6) Brand personality sincerity has significant effect on brand loyalty through brand love as mediation variable on Converse brand shoes users. (7) Brand personality excitement has significant effect on brand loyalty through brand love as mediation variable on Converse brand shoes users.